2007
DOI: 10.1159/000098445
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Cerebral Hemorrhage in Chinese Male Heavy Drinkers with Mild Liver Disorder

Abstract: Background: Epidemiological evidence suggests that heavy alcohol consumption increases the risk for either stroke or liver disease. The goal of this study was to determine whether heavy drinkers with mild liver disorder (MLD) are at risk of hemorrhagic stroke. Methods:All of the 524 patients recruited were males with a first-ever acute stroke and were consecutively admitted to the Tri-Service General Hospital between January 2000 and December 2001. The risk factors, liver function, stroke subtypes, and hemosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…1,26 Subjects with the ALDH2*2 allele have low enzyme activity that impairs acetaldehyde metabolism. 16 The resulting acute acetaldehyde accumulation induces strongly negative psychophysiological reactions, as well as cardiovascular responses, during low to moderate alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,26 Subjects with the ALDH2*2 allele have low enzyme activity that impairs acetaldehyde metabolism. 16 The resulting acute acetaldehyde accumulation induces strongly negative psychophysiological reactions, as well as cardiovascular responses, during low to moderate alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because it has multifactorial causes, 2 identification of its underlying pathogenesis and risk factors is essential. 3,4 As a part of the phase I oxidizing enzyme aldehyde dehydrogenase (ALDH) superfamily, ALDH2 is responsible for both ethanol metabolism and biogenic and xenogenic aldehyde detoxification.…”
mentioning
confidence: 99%
“…Therefore, hypertension and its risk factors are important in the development of ICH [11]. Additionally, previous case studies reported that ICH was associated with liver dysfunction [17,18] and elevated serum aminotransferase [4,5,6]. Elevated serum ALT is a sensitive, but nonspecific marker of hepatocellular injury and nonalcoholic fatty liver disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study in Japan, a high ALT level was associated with increased risk of lobar ICH [5]. Another study in Taiwan observed an association between mild liver disease and ICH [6]. Thus, the East Asian Network for Stroke Prevention Study (EANS) was established to investigate the association between liver disease and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…El consumo de alcohol, sobre todo la ingesta de importantes cantidades de manera regular (más de 300 gramos de alcohol por semana), parece lesionar en forma temprana (incluido en sujetos 16 jóvenes) los pequeños vasos . El riesgo probablemente se halle incrementado por los desórdenes de la hemostasia que presentan los consumidores crónicos de alcohol con afección de la funcionalidad 17 hepática .…”
Section: Introductionunclassified